2019
DOI: 10.2478/fhort-2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid and jasmonic acid can suppress green and blue moulds of citrus fruit and induce the activity of polyphenol oxidase and peroxidase

Abstract: The ability of salicylic acid and jasmonic acid to suppress post-harvest infection with green mould Penicillium digitatum and blue mould P. italicum on three citrus species Citrus reticulata 'Kinnow', C. limon 'Meyer Lemon', and C. limetta 'Mosambi' was evaluated in a dose-response study. Salicylic acid (SA) and jasmonic acid (JA) were applied to the fruits as a post-harvest dip treatment followed by wound inoculation with the pathogens. Both resistance inducers caused a significantly lower disease severity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…The temporal increase in POD activities was in line with the reductions in BRI and LD ( Figure 1 A,B). This result with MeJA was in line with the studies of Yao and Tian [ 34 , 35 ] and Moosa et al [ 119 ], in which the authors demonstrated that JA induced a stronger POD activity and decreased LD caused by M. fructicola , P. expansum and P. digitatum in sweet cherry, peach and citrus fruits, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The temporal increase in POD activities was in line with the reductions in BRI and LD ( Figure 1 A,B). This result with MeJA was in line with the studies of Yao and Tian [ 34 , 35 ] and Moosa et al [ 119 ], in which the authors demonstrated that JA induced a stronger POD activity and decreased LD caused by M. fructicola , P. expansum and P. digitatum in sweet cherry, peach and citrus fruits, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Oxidation of peroxidases results in a more rigid cell wall through the increased matrix of polysaccharide and glycoprotein molecules [ 112 , 115 ]. Thus, POD plays a key role in the reinforcement of cell walls; therefore, it can protect the cell wall against infection by fungal pathogens [ 116 , 117 , 118 , 119 ]. Our results indicated that postharvest treatments of SA and MeJA induced higher POD activities in M. laxa -inoculated apricot fruits compared with water-treated fruits ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, it was also noted that the incorporation of trans-cinnamaldehyde with poly(lactic acid) and poly(butylene adipate-co-terephthalate) provides better performance as an edible film [35]. Overall, results support the idea suggested by Moosa et al [36] where the biomaterials were reported as high potent against green and blue mold of citrus fruits. e MIC and MFC examinations are being applied as one of the most important indexes to access the inhibitory efficiency of antifungal chemicals.…”
Section: Antifungal Activity Of Cinnamaldehyde (Ca) and Its Derivativessupporting
confidence: 80%
“…It is not the only way for plants to resist pathogens; it can be combined with other ways to resist pathogen infection (Xia et al, 2015;Wang X. Y. et al, 2019). Several plant hormones are known to mediate plant defense responses against pathogens (Verma et al, 2016), of which the increase in concentration of SA and JA helps to enhance the activities of POD and PPO (Moosa et al, 2019). The results showed that inoculation with the AM fungus increased the concentrations of JA and SA in plants infected with pathogens.…”
Section: Discussionmentioning
confidence: 96%